Study and design of a coconut stripper - Claude Vodounnou, Edmond; Clarence Semassou, Guy; H. Ahouansou, Roger (International Journal of Basic and Applied Sciences, 2022)
The predominance of the primary sector is noticeable in the economy of most African countries, particularly in Benin. Thus, to make this sector a vector of wealth and development, it is imperative to think about the development of technologies to improve the efficiency of processing and product quality. The mechanization of this sector is therefore necessary to make it more competitive. In Benin we have a lot of products which are made with the coconut. This sector has been relegated to a non-priority plan, whereas the coconut palm is a plant with a very considerable value like the oil palm, of which all the derived products are usable. It seems necessary to pass to the revival of this sector to help to stabilize the incomes of the small producers and traders in particular and to improve the commercial balance of the country in general. The maximization of the output of this sector directs towards the formula of Lavoisier: "nothing is lost, nothing is created, everything is transformed". The application of this formula allows us to transform the by-products of the said product. Currently, the de-shearing of the coconut is done manually with a cutter or with a pointed object. This way of making is too painful for producers who have large exploitations of coconut trees. In order to make this sector more profitable, our end-of-training work focuses on the study and design of a coconut de-sheathing machine intended to accompany coconut producers by reducing their pains and increasing their productivity in order to enhance the transformation of the said product. Â Â